Meningkatkan Kesadaran Wirausaha Kepada Siswa SMPN Satu Atap Pulau Pari Melalui Kegiatan Pendidikan Kewirausahaan - Marfuah, Siti; Widayanti, Ari; Karsiwan, Wawan (Jurnal SOLMA, 2023)
Background: The demographic bonus is a very important momentum for all Indonesian people to prepare for, including the people on Pari Island, Seribu Islands. Education is a very important issue to be addressed and prepared optimally by the community and also the government on Pari Island, as a step towards welcoming a Golden Indonesia 2045. This activity aims to ensure that the people of Pari Island, especially children and teenagers, have a high entrepreneurial spirit and are good at maximize every opportunity that exists, increase creativity, innovation and a sense of independence. Method: Involving students at One Roof Pari Island Middle School with a learning method, namely a practical method where students are required to be directly and actively involved in making trinkets from beads. Results: The enthusiasm of students at One Roof State Middle School, Pari Island, was very high in the process of implementing the Entrepreneurship Education program as well as the follow-up to the Entrepreneurship Education program for students at One Roof State Middle School, Pari Island, namely the products of Entrepreneurship Education were exhibited at the 2023 Bahari KKN Expo. Conclusion: It is necessary to manage Pari Island as a tourist destination optimally by improving the quality of Human Resources through Entrepreneurship Education activities.